Respuesta :

Answer:

6 - 8x

Step-by-step explanation:

The question is:

(-3x + 4) - (5x - 2)

When you have two numbers inside a bracket, it is called a binomial. (Here we have two binomials). When you subtract a binomial, you "add the opposite".

To get rid of the second pair of brackets, add the opposite of 5x. Since 5x is positive, add negative 5x.

(-3x + 4) - (5x - 2)

= (-3x + 4) +-5x -(- 2)      A positive and a negative make a negative

= (-3x + 4) - 5x -(- 2)

Add the opposite of -2. The opposite of -2 is positive 2.

= (-3x + 4) - 5x -(- 2)

= (-3x + 4) - 5x ++ 2       Two positives make a positive

= (-3x + 4) - 5x + 2

Now you can remove all brackets.

= -3x + 4 - 5x + 2        Collect like terms

= 4 + 2 - 3x - 5x       Rearranged so you can see like terms

= 6 - 8x              Final answer

Answer:

6-8x

Step-by-step explanation:

Otras preguntas